2020
DOI: 10.3390/nu12020278
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Profile of Obese Diabetic Women Submitted to Roux-en-Y Gastric Bypass and Its Association with Food Intake and Postoperative Diabetes Remission

Abstract: Gut microbiota composition is influenced by environmental factors and has been shown to impact body metabolism. Objective: To assess the gut microbiota profile before and after Roux-en-Y gastric bypass (RYGB) and the correlation with food intake and postoperative type 2 diabetes remission (T2Dr). Design: Gut microbiota profile from obese diabetic women was evaluated before (n = 25) and 3 (n = 20) and 12 months (n = 14) after RYGB, using MiSeq Illumina-based V4 bacterial 16S rRNA gene profiling. Data on food in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 49 publications
3
36
3
1
Order By: Relevance
“…Concerning the last aspect, recent studies have shown that diet has an important role in shaping the gut microbiota [33][34][35]. According to previous studies that reported the correlation between colorectal and dietary factors [36], we believe dietary factors influenced our results. However, our study did not discuss the relation between the dietary and colorectal polyps because dietary variables were not directly measured.…”
Section: Discussionmentioning
confidence: 63%
“…Concerning the last aspect, recent studies have shown that diet has an important role in shaping the gut microbiota [33][34][35]. According to previous studies that reported the correlation between colorectal and dietary factors [36], we believe dietary factors influenced our results. However, our study did not discuss the relation between the dietary and colorectal polyps because dietary variables were not directly measured.…”
Section: Discussionmentioning
confidence: 63%
“…Nowadays, bariatric surgery is the most efficient method of obesity treatment [12]. Many studies have shown that bariatric surgery not only helps patients achieve long-term weight loss but also removes obesity-related complications, including T2DM and high blood pressure [13][14][15][16]. It has been demonstrated that weight-loss by laparoscopic sleeve gastrectomy leads to a 40%-65% reduction in excess weight.…”
Section: Introductionmentioning
confidence: 99%
“…[ 55 57 ] In addition to the alterations in microbial components, an increase in the gut microbial richness after RYGB was also uncovered in a clinical trial. [ 58 ] For the starting point and duration of the altered intestinal microbiome, a clinical trial detected and followed the alterations in gut microbiota in morbidly obese patients after RYGB. They showed that increased microbial diversity and altered composition could be observed within 3 months of RYGB and more than half of the changed bacteria were stable in relative abundance 1 year later.…”
Section: The Gut Microbiota Is Significantly Altered After Rygbmentioning
confidence: 99%
“…Studies have reported a possible association between RYGB-induced microbial changes and human metabolic indices in plasma. [ 58 , 60 ] Murphy et al [ 61 ] found that there were no phyla level changes in patients with persisting diabetes 1 year after RYGB; in those who achieved diabetes remission after RYGB, there were three significant changes at the phyla level (increases in Firmicutes and Actinobacteria, decrease in Bacteroidetes) and 13 significant changes at the species level. In another study, significant correlations were found between plasma glucose with Faecalibacterium prausnitzii , as well as HbA1c with Trichothecium roseum and Veillonella parvula.…”
Section: The Gut Microbiota Is Significantly Altered After Rygbmentioning
confidence: 99%